Pengaruh Motivasi, Stress Kerja dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan pada Balai Penyelidikan dan Pengembangan Teknologi Kebencanaan Geologi (BPPTKG) Daerah Istimewa Yogyakarta - Agista Wigi Nuroini; Kusuma Chandra Kirana; Syamsul Hadi (Universitas Batanghari, 2023)
This study aims to determine and evaluate the effect of motivation, work stress, and physical work environment on employee performance at the Center for Research and Development of Geological Disaster Technology (BPPTKG) Special Region of Yogyakarta. The sample in this study were employees of the Special Region of Yogyakarta Special Region of Yogyakarta with 70 respondents. The sampling technique applied is non-probability sampling where all members of the population are sampled. Data collection was carried out through questionnaires. The data analysis method used in this study is multiple linear regression analysis which aims to calculate the magnitude of the regression coefficient to show the magnitude of the influence of motivation, work stress and physical work environment on employee performance. While the observation test shows that various changes in motivation, work stress and physical work environment jointly affect employee performance in the special area of the Geological Disaster Technology Investigation and Development Agency (BPPTKG) Special Region of Yogyakarta. The results of this research show that: (1) motivation has no significant effect on employee performance; (2) work stress has no significant effect on employee performance; (3) the physical work environment has a significant effect on employee performance.